1986
DOI: 10.1159/000234127
|View full text |Cite
|
Sign up to set email alerts
|

Local Intranasal Immunotherapy with High-Dose Polymerized Ragweed Extract

Abstract: Thirty-one ragweed-allergic patients received preseasonal local intranasal immunotherapy (LNIT) with high doses of gluteraldehyde-polymerized ragweed extract (average total dose 544 μgantigen E). Minimal side effects were reported during treatment and did not interfere with the dosing schedule. During the ragweed pollen season, LNIT-treated patients had lower symptom scores for sneezing, rhinorrhea and nasal congestion than a comparable group of untreated ragweed-allergic patients. There was no difference in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The published studies agree on the clinical efficacy of LNIT (Table 1): a clinical improvement (symptordmedication scores) was constantly observed in the actively treated groups, although depending upon the type of extract used. Actually, treatments employing low doses appeared to be less effective than those with higher dosages (13,14) and aqueous extracts were observed to be more effective than modified extracts (10,12,24).…”
Section: Experimental Results: Efficacy Safety Side Effectsmentioning
confidence: 99%
“…The published studies agree on the clinical efficacy of LNIT (Table 1): a clinical improvement (symptordmedication scores) was constantly observed in the actively treated groups, although depending upon the type of extract used. Actually, treatments employing low doses appeared to be less effective than those with higher dosages (13,14) and aqueous extracts were observed to be more effective than modified extracts (10,12,24).…”
Section: Experimental Results: Efficacy Safety Side Effectsmentioning
confidence: 99%
“…Detection of IgE-reactive components in the systemic circulation when an allergenic extract is given intranasally introduces a new element of discussion about the possible mechanisms by which this form of treatment, recently proposed as an alternative to the parenteral route, produces clinical efficacy in rhinitic patients (15,19,21,30,33). Various hypotheses have been put forward: a common finding in allergic patients after local therapy is a rise in the threshold value as determined by specific provocation tests at the target organ, while the induction of local immunological protection (IgA and IgG blocking antibodies) is suggestive, but results are still contradictory (12,15). Recent studies in mice and rats showed that repeated inhalation of aerosols containing egg albumin or ragweed antigens induced a transient IgE response which switched oii spontaneously despite continuous exposure (10,13,26).…”
Section: Discussionmentioning
confidence: 99%
“…2) The effectiveness of local immunotherapy (1,2,5,7,8,13,17). This kind of treatment causes an increase of threshold dosage and a significant decrease of hyperreactivity symptoms (rhinorrhoea and obstruction).…”
Section: Discussionmentioning
confidence: 99%